Komunikasi Krisis Dalam Organisasi: Analisis Naratif Tentang Pengelolaan Konflik Internal - Almadina Rakhmaniar (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This research aims to examine internal conflict management in organizations through narrative analysis of crisis communication. Qualitative methods were used to understand the causes of conflict, crisis management strategies, leadership roles, the impact of conflict, communication techniques used, and policies and procedures implemented in the organization. Data were collected through in-depth interviews, participatory observation, and document analysis. The results revealed that internal conflicts are often caused by differences in interests, lack of effective communication, and organizational change. Effective crisis management strategies involve open communication, mediation, and a proactive approach. Responsive and thoughtful leadership plays a key role in conflict resolution. Poorly managed conflict negatively impacts productivity, employee morale, and team collaboration, and damages the organization's image. Communication techniques such as collaborative approaches and assertive communication are essential in managing crises. The practical implications of these findings are the need for the development of clear conflict resolution policies, conflict management training, promotion of open communication, and periodic evaluation of policy effectiveness. With a comprehensive approach, organizations can improve work dynamics and strengthen teamwork.